Why Did Cantillon Change the Meaning of Entrepreneurship? - Thornton, Mark (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2019)
In breaking with the policy regime of mercantilism, Richard Cantillon put forth a manuscript in 1730, wherein he produced the first treatise of economic theory. Key to this development was his new theory of entrepreneurship which allowed him to construct economic theories and concepts. Recent research has shown that he did not coin the term, but rather radically changed the meaning of an existing term, to its near opposite. This paper explores why he changed the meaning of the entrepreneur. The speculative answer is both theoretical and based on his life experience.